Description of Phytoplankton from the Bolshoy Cheremshan River (Kuybyshev Reservoir) - O.G. Gorokhova (Учёные записки Казанского университета: Серия Естественные науки)
The results of the study (2012) of phytoplankton from the Bolshoy Cheremshan River, a tributary of the Kuybyshev Reservoir, have been considered. A total of 147 species of 8 divisions have been revealed. The highest species diversity and abundance have been observed in Bacillariophyta and Chlorophyta. The structure of algocenoses has been found to be dominated by small-celled centric diatoms, green chlorococcales, and cryptomonads. All species identified in this study are characteristic of eutrophic wa-ters. According to the saprobic indices, the studied river belongs to β-mesosaprobic zone. Data clustering by comparing the composition of dominant phytoplankton species has made it possible to spot differences between the river reaches. The influence of human settlements on the structure of planktonic algocenoses has been discovered.